Roald Dahl Little Library. 3, Numbers - Dahl, Roald (Puffin Books, 2019)
ONE enormous crocodile, TWO little mice, THREE mischievous monkeys . . .Learn whizzpopping numbers, splendiferous colours, glorumptious opposites, and meet phizz-whizzing creatures from the world of Roald Dahl. A delightful treat for curious little hands, this little library is perfect for introducing titchy toddlers to new concepts, and to the imaginative world of Roald Dahl.